A particle‐based method for mechanical analyses of planar fiber‐based materials. (28th January 2013) - Persson, J.; Isaksson, P.
SUMMARY A new discrete element model to deal with rapid deformation and fracture of flat fibrous materials is derived. The method is based on classical mechanical theories and is a combination of traditional particle dynamics and nonlinear engineering beam theory. It is assumed that a fiber can be seen as a beam that is represented by discrete particles, which are moving according to Newton's laws of motion. Damage is dealt with by fracture of fiber‐segments and fiber–fiber bonds when the potential energy of a segment or bond exceeds the critical fracture energy. This allows fractures to evolve as a result of material properties only. To validate the model, four examples are shown and compared with analytical results found in literature. Copyright © 2013 John Wiley & Sons, Ltd.